Dziecko z FASD – terapia neurologopedyczna - Pawłowska-Jaroń, Halina; Orłowska-Popek , Zdzisława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The article characterises Fetal Alcohol Spectrum Disorders as a holistic developmen- tal disorder, emphasising the importance of communication difficulties, both verbal and non-verbal. By pointing successively to the pathological changes in the anatomy and the functioning of individual parts of the CNS, the authors draw attention to the aspects of the impaired development of a child with FASD (FAS, PFAS, ND-PAE, FAS without confirmed prenatal alcohol exposure) and the possibility of providing support through proper programming of the therapeutic process while taking into consider- ation neurobiological knowledge. In the therapeutic work with a child affected by fetal alcohol syndrome, the starting point should be the identification of the child’s strengths rather than deficits. These children require holistic therapy, thanks to which it is pos- sible to eliminate the health, communication and also social problems. The authors present the methods of overall development interactions with the aim of creating the foundations of the language.